IDENTIFIKASI POSISI CRACKS DAN PENGARUHNYA TERHADAP PERUBAHAN STABILITAS LERENG - Jarkani, Jarkani; Alexsander, Stephanus; Sarie, Fatma; Yani, Mohammad Ikhwan; Hendri, Okrobianus (Fakultas Teknik Universitas Palangka Raya, 2025)
Slope is the difference in elevation of a land surface with a varying angle of inclination. Disasters that commonly occur on slopes are landslides caused by the loss of stability on a slope. One of the determinants of slope stability is the strength of the material that makes up the slope to resist collapse. Generally, slope stability analysis only refers to the values of cohesion (c) and soil shear angle (ø), without taking into account the weak plane on the slope. Landslides that occur on slopes generally occur partially. Partial landslides are caused by the presence of weak areas on the slope. The process of identifying weak areas in the slope uses the geoelectric method. The use of geo-electrical methods through field surveys in the form of resistivity tomography aims to model 2D subsurface layers so that it is known which layers have the potential to become weak areas in the form of cracks in the slope. While the process of identifying changes in slope stability due to the presence of weak areas based on the position of cracks using the help of FEM (finite element method) software The purpose of this research is to identify the weak plane of the slope based on the position of cracks and their effect on slope stability. The results of geoelectric testing showed the presence of weak areas in the form of cracks formed in the slope based on the resistivity value of (731.28–1712.55) Ωm. The results of the analysis of changes in slope stability due to the presence of weak areas in the form of cracks in the slope show a decrease in the safety factor (SF) value, which previously had a safety factor (SF) value of 4.272 to 3.630.